2018
DOI: 10.1016/j.neurobiolaging.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive response to fish oil, blueberry, and combined supplementation in older adults with subjective cognitive impairment

Abstract: Given evidence that eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), and anthocyanin-rich blueberries provide neurocognitive benefit, we investigated long-term supplementation in older adults with cognitive complaints. In a 24-week randomized, double-blind, placebo-controlled trial, elderly men and women received daily fish oil (FO) or blueberry (BB) or both. Diet records confirmed that participants reduced background consumption of EPA, DHA, and anthocyanins as prescribed. Erythrocyte EPA + DHA compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 66 publications
1
82
1
Order By: Relevance
“…Small RCTs ( n = 26–37) with blueberry nutraceuticals have shown oral intake of a concentrate containing either 387 mg of anthocyanidins or 12 g of lyophilised blueberries for 12 weeks improves cognitive abilities in healthy older adults (Bowtell, Aboo‐Bakkar, Conway, Adlam, & Fulford, ; Miller, Hamilton, Joseph, & Shukitt‐Hale, ). Larger RCTs ( n = 94–122) also conclude that blueberry extracts improve memory performance in older adults when taken for periods of 3 to 6 months (McNamara et al, ; Whyte, Cheng, Fromentin, & Williams, ). Other RCTs have concluded that flavonoid‐rich citrus juices improve cognitive functions in healthy older adults ( n = 37) after 8 weeks of intake (Kean et al, ) and in healthy middle‐aged adults ( n = 22) after acute administration (Alharbi et al, ).…”
Section: Phytochemicals As Nutraceuticalsmentioning
confidence: 99%
“…Small RCTs ( n = 26–37) with blueberry nutraceuticals have shown oral intake of a concentrate containing either 387 mg of anthocyanidins or 12 g of lyophilised blueberries for 12 weeks improves cognitive abilities in healthy older adults (Bowtell, Aboo‐Bakkar, Conway, Adlam, & Fulford, ; Miller, Hamilton, Joseph, & Shukitt‐Hale, ). Larger RCTs ( n = 94–122) also conclude that blueberry extracts improve memory performance in older adults when taken for periods of 3 to 6 months (McNamara et al, ; Whyte, Cheng, Fromentin, & Williams, ). Other RCTs have concluded that flavonoid‐rich citrus juices improve cognitive functions in healthy older adults ( n = 37) after 8 weeks of intake (Kean et al, ) and in healthy middle‐aged adults ( n = 22) after acute administration (Alharbi et al, ).…”
Section: Phytochemicals As Nutraceuticalsmentioning
confidence: 99%
“…Similarly, it has been observed that blueberry powder (Vaccinium sp.) supplementation in patients with Alzheimer's disease and cognitive decline reduces the self-reported inefficiencies in daily functioning [90] (Table 3).…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…The details of the studies are provided in Table 2 Table 2. Few authors investigated the beneficial effects of variable doses / combinations of DHA and reported as larger study [24][25][26][27]. Data from each of these sub studies (doses / combinations of DHA) were extracted and used as separate studies.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Overall studies report over 80% adherence to the intervention. Due to unavailability of dispersion data (such as SD / CI) for various cognitive assessments, McNamara et al (2018) was not part of the Meta-analysis (quantitative results) however was considered as part of the review (qualitative results) [26].…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation